Pushover Analysis of 6-Floors Irregular Building Structure (Case Study: Fave Hotel Building-Padang City, West Sumatra) - Redha Arima R.M*; Romi Sani Saputra; Masrilayanti Masrilayanti; Ruddy Kurniawaran (Universitas Syiah Kuala, 2023)
Most of Indonesia is located in earthquake areas with moderate to high intensity, one of which is Padang city. The capital city of West Sumatra is an area that is very prone to earthquakes because it is located between two active plates of the world. The big earthquake that ever occurred in Padang City measuring ± 7.9 SR on September 30, 2009, caused several buildings to experience structural failure, buildings were destroyed and completely damaged. In earthquake-resistant buildings, the geometry of the building structure plan is very influential in responding to earthquake forces. Regular, simple, and symmetrical buildings have a better response to earthquakes than irregular buildings (Pauly and Preisly, 1992). This study analyzes one of the existing irregular hotel building structures in Padang city using the ETABS V.16.2 program. The analysis was carried out using the PBD method, namely non-linear pushover based on the Applied Technology Council (ATC-40), FEMA 356, and FEMA 440. The purpose of this study was to evaluate the capacity of the review building structure due to the influence of earthquake forces, including the failure mechanism. From the results of the research, the maximum shear force that the structure can withstand is 18344,6041 kN with a displacement of 291,435 mm due to Push-X, and 18611.7226 kN with a displacement value of 190,459 mm due to Push-Y. The displacement that occurs is still below the permit displacement, which is 2% x H, which is 442 mm. The maximum total drift is 0.013 in the X direction, 0.010 in the Y direction, and the maximum In-elastic drift is 0.011 in the X 0.006 in the Y direction, so based on the Drift Limitation parameter of the performance level, the review building structure is included in the Damage Control (DC) level.